Safety and efficacy of mass drug administration with a single-dose triple-drug regimen of albendazole + diethylcarbamazine + ivermectin for lymphatic filariasis in Papua New Guinea: An open-label, cluster-randomised trial. - Livingstone Tavul; Moses Laman; Cade Howard; Bethuel Kotty; Anna Samuel; Catherine Bjerum; Kobie O'Brian; Steven Kumai; Matthew Amuga; Lina Lorry; Zebedee Kerry; Melvin Kualawi; et al. (Public Library of Science (PLoS), 2022)
Background Papua New Guinea (PNG) has a high burden of lymphatic filariasis (LF) caused by Wuchereria bancrofti, with an estimated 4.2 million people at risk of infection. A single co-administered dose of ivermectin, diethylcarbamazine and albendazole (IDA) has been shown to have superior efficacy in sustained clearance of microfilariae compared to diethylcarbamazine and albendazole (DA) in small clinical trials. A community-based cluster-randomised trial of DA versus IDA was conducted to compare the safety and efficacy of IDA and DA for LF in a moderately endemic, treatment-naive area in PNG. Methodology All consenting, eligible residents of 24 villages in Bogia district, Madang Province, PNG were enrolled, screened for W. bancrofti antigenemia and microfilaria (Mf) and randomised to receive IDA (N = 2382) or DA (N = 2181) according to their village of residence. Adverse events (AE) were assessed by active follow-up for 2 days and passive follow-up for an additional 5 days. Antigen-positive participants were re-tested one year after MDA to assess treatment efficacy. Principal findings Of the 4,563 participants enrolled, 96% were assessed for AEs within 2 days after treatment. The overall frequency of AEs were similar after either DA (18%) or IDA (20%) treatment. For those individuals with AEs, 87% were mild (Grade 1), 13% were moderate (Grade 2) and there were no Grade 3, Grade 4, or serious AEs (SAEs). The frequency of AEs was greater in Mf-positive than Mf-negative individuals receiving IDA (39% vs 20% p<0.001) and in Mf-positive participants treated with IDA (39%), compared to those treated with DA (24%, p = 0.023). One year after treatment, 64% (645/1013) of participants who were antigen-positive at baseline were re-screened and 74% of these participants (475/645) remained antigen positive. Clearance of Mf was achieved in 96% (52/54) of infected individuals in the IDA arm versus 84% (56/67) of infected individuals in the DA arm (relative risk (RR) 1.15; 95% CI, 1.02 to 1.30; p = 0.019). Participants receiving DA treatment had a 4-fold higher likelihood of failing to clear Mf (RR 4.67 (95% CI: 1.05 to 20.67; p = 0.043). In the DA arm, a significant predictor of failure to clear was baseline Mf density (RR 1.54; 95% CI, 1.09 to 2.88; p = 0.007). Conclusion IDA was well tolerated and more effective than DA for clearing Mf. Widespread use of this regimen could accelerate LF elimination in PNG. Trial registration Registration number NCT02899936; https://clinicaltrials.gov/ct2/show/NCT02899936.